Prolonged drought changes the bacterial growth response to rewetting. (September 2015) - Meisner, Annelein; Rousk, Johannes; Bååth, Erland
Abstract: Rewetting a dry soil can result in two response patterns of bacterial growth and respiration. In type 1, bacterial growth starts to increase linearly immediately upon rewetting and respiration rates are highest immediately upon rewetting. In type 2, bacterial growth starts to increase exponentially after a lag period with a secondary increase in respiration occurring at the start of the exponential increase in growth. We previously observed that the type 1 response occurred after rewetting 4-day dried soil and type 2 for 1-year dried soil. Here we studied in detail how the duration of drought related to the two types of responses of bacterial growth and respiration to rewetting. Soil was air dried for different time periods from 4 days up to 48 weeks. Upon rewetting, bacterial growth and respiration was measured repeatedly at 17 °C during one week. Drought periods of ≤2 weeks resulted in a type 1 response whereas drought periods of ≥4 weeks resulted in a type 2 response. The lag period increased with drought duration and reached a maximum of ca. 18 h. The bacterial growth response was also affected by incubation of moist soil before drying–rewetting. The lag period increased with duration of moist soil incubation before the 4-day drying–rewetting event and reached also a maximum of ca. 18 h. The exponential growth increase in the type 2 response coincided with a secondary increase in respiration, which increased in magnitude with increasing drought duration. Cumulative respiration increased with drought duration and was ca. 4 times higher after 48 weeks of drought compared to 4 days. Thus, prolonged drought affected the response type of bacterial growth and respiration to rewetting, and also increased lag period, the magnitude of the secondary increase in respiration and total C release. The effect of drought was, however, modified by the lenght of the incubation period of moist soil before drought, suggesting that soil conditions before a drying–rewetting event need consideration when evaluating microbial responses. Graphical abstract: Bacterial growth upon rewetting soils dried for 4 days up to 48 weeks. The lag period before bacterial growth increased with duration of drought. Highlights: Soils were dried from 4 days up to 48 weeks before rewetting. Bacterial growth and respiration were measured during one week upon rewetting. Longer drought induced, and increased duration of a lag period before growth. The cumulative respiration after rewetting increased with duration of drought. Incubation of moist soil before drying–rewetting also induced a lag period.